Pedagogical Reinterpretation of Kakawin Nilacandra for Deep Learning: A Model of Hindu Character Education - Heny Perbowosari,; Purwanto, Heri; Sandhya Tiwari, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
A Deep Learning approach based on mindfulness, meaningfulness, and joy has become a focus of educational transformation in Indonesia; however, integrating this modern concept with local wisdom remains a challenge. This study presents a pedagogical reinterpretation of Kakawin Nilacandra, a Balinese literary work that narrates King Nīlacandra’s spiritual journey toward wisdom, self-control, and ethical leadership through Śiwa-Buddha teachings. Using a qualitative approach, the study employs content analysis and hermeneutic interpretation, supported by triangulation and textual evidence. The findings reveal that Kakawin Nilacandra embodies educational values closely aligned with Deep Learning principles. The reinterpretation identifies three sequential learning stages: self-awareness, self-transformation, and self-internalization. It also demonstrates the text's relevance to teaching modules and its potential application in language, character, history, and citizenship education. These findings highlight how the reinterpretation of local literary wisdom can contribute to culturally grounded pedagogical innovation and support the implementation of Deep Learning in Indonesia.
Keywords: deep learning; Hindu character education; Kakawin Nilacandra; pedagogical reinterpretation; local wisdom